Decreased cortical spreading depolarizations in neurosurgical patients being given ketamine. (January 2013) - Carlson, Andrew P; Shuttleworth, C William
Evaluation of: Hertle DN, Dreier JP, Woitzik J et al. ; Cooperative Study of Brain Injury Depolarizations (COSBID). Effect of analgesics and sedatives on the occurrence of spreading depolarizations accompanying acute brain injury. Brain 135(Pt 8), 2390–2398 (2012). This retrospective review by the Cooperative Study of Brain Injury Depolarizations group of 115 patients correlates the occurrence of cortical spreading depolarization (SD), measured with cortical electrodes, with the type of sedation used during monitoring in the intensive care unit. SD has recently been implicated in the progression of acute brain injury, and this study represents the first systematic approach to attempt to understand whether the deleterious effects of SD can be impacted with drug therapy. A significantly decreased probability of SD occurrence was documented with ketamine, but none of the five other drugs that were studied. This effect was seen across all days of monitoring and seemed to have a dose-dependent effect. In evaluating clusters of SD (which most likely contribute to injury progression), ketamine remained significantly associated with decreased likelihood of clusters, along with a weaker effect with propofol and a surprising positive association with midazolam. Owing to the retrospective nature of the study, no causal association can be concluded, although the suppressive effect of NMDA receptor antagonists is consistent with prior animal data. This work will provide critical clinical groundwork for carefully designed clinical trials focused on SD suppression and outcome.